Diabetes, Oxidative Stress, and DNA Damage Modulate Cranial Neural Crest Cell Development and the Phenotype Variability of Craniofacial Disorders - Fitriasari, Sharien; Trainor, Paul A. (Frontiers in Cell and Developmental Biology, 2021)
Craniofacial malformations are among the most common birth defects in humans and they often have significant detrimental functional, aesthetic and social consequences. To date, more than 700 distinct craniofacial disorders have been described. However, the genetic, environmental and developmental origins of most of these conditions remain to be determined. This gap in our knowledge is hampered in part by the tremendous phenotypic diversity evident in craniofacial syndromes but is also due to our limited understanding of the signals and mechanisms governing normal craniofacial development and variation. The principles of Mendelian inheritance have uncovered the etiology of relatively few complex craniofacial traits and consequently, the variability of craniofacial syndromes and phenotypes both within families and between families is often attributed to variable gene expression and incomplete penetrance. However, it is becoming increasingly apparent that phenotypic variation is often the result of combinatorial genetic and non-genetic factors. Major non-genetic factors include environmental effectors such as pregestational maternal diabetes, which is well-known to increase the risk of craniofacial birth defects. The hyperglycemia characteristic of diabetes causes oxidative stress which in turn can result in genotoxic stress, DNA damage, metabolic alterations, and subsequently perturbed embryogenesis. In this review we explore the importance of gene-environment associations involving oxidative stress and DNA damage during development, which may underpin the phenotypic variability observed in specific craniofacial syndromes.